Levantamento de tecnologias tradicionais no município de Ponta de Pedras, ilha de Marajó, Pará: estudo de caráter etnoarqueológico. - Malato, Roberto Coutinho (Museu Paraense Emílio Goeldi, 2022)
The caboclo ceramics, the cultivation of manioc and the manufacturing of flour, the use of braiding and basketry techniques are traditional technologies used in the communities of Praia Grande and Mangabeira, located in the municipality of Ponta de Pedras. With the study of these caboclo communities, we aim to obtain subsidies for a better interpretation of the prehistoric past and to determine subsistence patterns of the autochthonous populations of the municipality through the comparative analysis of cultural material and other archeological evidence. In Ponta de Pedras there are sites such as the "Teso do Bode", whose cultural material will allow a comparative ethno-archaeological study. As concrete results we will present the register of traditional techniques for the manufacture of pottery and the location of some archeological sites in the municipality of Ponta de Pedras. Once the excavation has been carried out, the ceramic material will be analyzed in the laboratory in order to determine the sequence of pottery groups in the region. The cultural material from the excavations will also allow absolute dates to be obtained, thus situating the cultures temporally and spatially.